What will become of reproductive issues in Trump's America?. Issue 49 (1st January 2017) - Joffe, Carole
Abstract: The election of Donald Trump to the presidency came as a severe and unexpected shock to the already beleaguered pro-choice movement in the US. This article will review what the president-elect said during the campaign about abortion and what his administration is likely to do after his inauguration.